A global report on the dynamics of COVID-19 with quarantine and hospitalization: A fractional order model with non-local kernel. (June 2022) - Ahmad, Zubair; El-Kafrawy, Sherif A.; Alandijany, Thamir A.; Giannino, Francesco; Mirza, Ahmed A.; El-Daly, Mai M.; Faizo, Arwa A.; Bajrai, Leena H.; Kamal, Mohammad Amjad; Azhar, Esam I.
Abstract: In this paper, a compartmental mathematical model has been utilized to gain a better insight about the future dynamics of COVID-19. The total human population is divided into eight various compartments including susceptible, exposed, pre-asymptomatic, asymptomatic, symptomatic, quarantined, hospitalized and recovered or removed individuals. The problem was modeled in terms of highly nonlinear coupled system of classical order ordinary differential equations (ODEs) which was further generalized with the Atangana-Balaeanu (ABC) fractional derivative in Caputo sense with nonlocal kernel. Furthermore, some theoretical analyses have been done such as boundedness, positivity, existence and uniqueness of the considered. Disease-free and endemic equilibrium points were also assessed. The basic reproduction was calculated through next generation technique. Due to high risk of infection, in the present study, we have considered the reported cases from three continents namely Americas, Europe, and south-east Asia. The reported cases were considered between 1st May 2021 and 31st July 2021 and on the basis of this data, the spread of infection is predicted for the next 200 days. The graphical solution of the considered nonlinear fractional model was obtained via numerical scheme by implementing the MATLAB software. Based on the fitted values of parameters, the basic reproduction number ℜ 0 for the case of America, Asia and Europe were calculated as ℜ 0 ≈ 2.92819, ℜ 0 ≈ 2.87970 and ℜ 0 ≈ 2.23507 respectively. It is also observed that the spread of infection in America is comparatively high followed by Asia and Europe. Moreover, the effect of fractional parameter is shown on the dynamics of spread of infection among different classes. Additionally, the effect of quarantined and treatment of infected individuals is also shown graphically. From the present analysis it is observed that awareness of being quarantine and proper treatment can reduce the infection rate dramatically and a minimal variation in quarantine and treatment rates of infected individuals can lead us to decrease the rate of infection. Graphical Abstract: ga1 Highlights: The model is generalized by implementing the Atangana-Baleanu fractional differential operator of Mittag-Leffler type kernel. Numerical scheme is implemented through MATLAB software for the graphical solution. Cases reported Asia, America and Europe are considered in this investigation between 1st May 2021 and 30th July 2021. Based on previous data, the spread of infection is predicted for the next 200 days which is shown through different graphs. In addition, the impact of quarantine and treatment on infected people is dramatically depicted.